Enhanced Osteogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells by a Hybrid Hydroxylapatite/Collagen Scaffold - Mazzoni, Elisa; Mazziotta, Chiara; Iaquinta, Maria Rosa; Lanzillotti, Carmen; Fortini, Francesca; D’Agostino, Antonio; Trevisiol, Lorenzo; Nocini, Riccardo; Barbanti-Brodano, Giovanni; Mescola, Andrea; Alessandrini, Andrea; Tognon, Mauro; et al. (Frontiers in Cell and Developmental Biology, 2021)
Human bone marrow-derived mesenchymal stem cells and their derivative eGFP-hBMSCs were employed to evaluate an innovative hybrid scaffold composed of granular hydroxylapatite and collagen hemostat (Coll/HA). The cellular morphology/cytoskeleton organization and cell viability were investigated by immunohistochemistry (IHC) and AlamarBlue metabolic assay, respectively. The expression of osteopontin and osteocalcin proteins were analyzed by IHC and E.L.I.S.A., whereas osteogenic genes were investigated by Q-PCR. Cell morphology of eGFP-hBMSCs was indistinguishable from parental hBMSCs. The cytoskeleton architecture of hBMSCs grown on the scaffold appeared to be well organized, whereas its integrity remained uninfluenced by the scaffold during the time course. Metabolic activity measured in hBMSCs grown on biomaterial was increased during the experiments, up to day 21 (p<0.05). The biomaterial induced the matrix mineralization in hBMSCs. The scaffold favored the expression of osteogenic proteins, such as osteocalcin and osteopontin. In hBMSC cultures, the scaffold induced up-regulation in specific genes that are involved in ossification process, (BMP2/3, SPP1, SMAD3 and SP7), whereas they showed an up regulation of MMP9 and MMP10 that play a central role during the skeletal development. HBMSCs were induced to chondrogenic differentiation trough up regulation of COL2A1 gene. Our experiments suggest that the innovative scaffold tested herein provides a good microenvironment for hBMSCs adhesion, viability and osteoinduction. HBMSCs is an excellent in vitro cellular model to assay scaffolds, which can be employed for bone repair and bone tissue engineering.